2010
DOI: 10.1177/0018720810368806
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Performance With 3-D Auditory Cues: Effects of Motion, Target Location, and Practice

Abstract: Operators in dynamic environments, such as aircraft cockpits, ground vehicles, and command-and-control centers, could benefit greatly from 3-D auditory technology when searching their environments for visual targets or other time-critical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…In fact, detailed analyses, considering the no sound condition as the baseline, demonstrated that participants particularly benefitted from the presentation of a congruent auditory cue when visual targets were localised in the left or right peripheral areas of the visual search field, the same areas for which they showed higher tone localisation accuracies. A larger benefit of congruent tones on target detection performance with increasing target eccentricity is also compatible with the results of previous studies (e.g., [ 3 , 50 ]). Moreover, on a group level, the participants did not significantly benefit from congruent auditory cues when the visual targets were presented in the left or the right central areas of the visual search field, the same areas in which their auditory localisation capability was considerably less accurate.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, detailed analyses, considering the no sound condition as the baseline, demonstrated that participants particularly benefitted from the presentation of a congruent auditory cue when visual targets were localised in the left or right peripheral areas of the visual search field, the same areas for which they showed higher tone localisation accuracies. A larger benefit of congruent tones on target detection performance with increasing target eccentricity is also compatible with the results of previous studies (e.g., [ 3 , 50 ]). Moreover, on a group level, the participants did not significantly benefit from congruent auditory cues when the visual targets were presented in the left or the right central areas of the visual search field, the same areas in which their auditory localisation capability was considerably less accurate.…”
Section: Discussionsupporting
confidence: 91%
“…Each stimulus image had only one search target. The two types of search targets used were a Landolt C Ring with a gap on the left or right, which were similar to those used by McIntire, Havig, Watamaniuk, and Gilkey (2010). The size of the gap in the target ring was 0.22 degrees of visual angle.…”
Section: Stimulus Materialsmentioning
confidence: 99%
“…Although specific tasks can be done by automated vision system, human vision still plays a vital role in industrial inspection, military target acquisition and video display tasks (Nalanagula et al 2006, Marmaras et al 2008, Koller, et al 2009, Mclntire et al 2010, Kujala and Saariluoma 2011. The visual lobe is an important aspect of human vision and is used to define the limit of peripheral sensitivity for particular target and background characteristics in a single glimpse/fixation without eye scanning movements.…”
Section: Introductionmentioning
confidence: 99%